Islamic Counseling and Educational Integration: A Holistic Model from Indonesian Pesantren - Heri Azmi; Lahmuddin Lubis; Abdurrahman Abdurrahman (Journal La Edusci, 2026)
The dominance of Western-centric paradigms in mental health and educational counseling has often marginalized spiritual and communal dimensions that are essential to non-Western societies. This study aims to examine the integration of Islamic counseling and education within the unique educational ecosystem of Indonesian pesantren, focusing on three modern institutions: Darul Arafah Raya, Nurul Hikmah An-Nahdly, and Darul Ihsan in North Sumatra. Employing a qualitative multiple case study design, data were collected through in-depth interviews, participant observation, and document analysis to explore how counseling is embedded within educational practices. The findings reveal that Islamic counseling is not implemented as a separate service but is systematically integrated into the educational process, encompassing classroom learning, dormitory life, and religious activities. This integration fosters a holistic model of student development that combines spiritual, emotional, and social dimensions. Core values such as sabr (patience), tawakkal (reliance on God), and muhasabah (self-reflection) function as pedagogical tools for emotional regulation and character formation, continuously reinforced through structured programs and daily interactions. The effectiveness of this model is further supported by institutional synergy among kyai, teachers, counselors, and dormitory supervisors, creating a comprehensive and collaborative educational environment. Unlike conventional Western approaches that tend to separate counseling from instructional processes, this model represents a proactive and value-driven framework that integrates counseling into the core of educational practice. The study concludes that the integration of Islamic counseling and education offers a culturally responsive and sustainable approach to holistic student development, contributing to the broader discourse on decolonizing educational and counseling practices.